Assessing tourist satisfaction, future behavior, and destination image: a case study of Pantai Pasir Putih in Blitar - Rohsuli Edi Peni; Cynthia Yohanna Kartikasari; Idfi Setyaningrum (Jurnal Pariwisata Pesona, 2024)
The rapid growth of the tourism industry in Indonesia has prompted the government to actively engage in efforts to develop the tourism sector to stimulate economic growth. One of the developments in the industry is the construction of the Southern Cross Road in several cities or districts. For example, Blitar Regency is renowned for its beautiful beaches, one of which is Pasir Putih Beach. This study measures the relationship between visitor satisfaction and future Behavior or recommendations to other tourists regarding destination image. Data for this study were obtained through questionnaires to individuals who have visited Pasir Putih Beach in Blitar Regency, with 200 questionnaires distributed. The data were analyzed using Structural Equation Modeling (SEM). The findings indicate that visitor satisfaction has a positive impact on destination image. Moreover, visitor satisfaction positively influences future Behavior in recommending Pasir Putih Beach to other tourists. Additionally, future Behavior positively impacts destination image and contributes to the economic benefits of individuals directly involved in tourism activities. Thus, an increase in tourist arrivals not only increases local revenue through tourism levies and taxes, but also creates business opportunities for local communities, creating a positive multiplier effect in the local economy around tourism destinations.